A Comparative Performance of Equity Funds, LTFs, and RMFs in Thailand - Taveesaengsakulthai, Piyawan (2008)
Thai mutual fund market is increasingly growing, especially Retirement Mutual Funds (RMFs) and Long-term Equity Funds (LTFs). Today RMFs and LTFs receive considerable attention due to their tax benefit provided for investors. The growth of RMFs and LTFs is one of the factors that contribute to the growth of Thai capital market. This paper examines the performance of RMFs and LTFs in the comparison with non-tax benefit equity funds (EQs) for the period January 2005 to December 2007. We found that most of funds exhibit no stock-selection ability. Additionally, on average, RMFs can significantly outperform the market on the risk-adjusted performances- Sharpe and Treynor measures. LTFs and EQs'performances are not significantly different from the market for these two indices. Morever, the differences in term of risk-adjusted performances among RMFs, LTFs and EQs are not statistically significant. However, when taking their tax-exempted benefit into account,investing in RMFs and LTFs reduces the cost of investment; hence, increases total rate of return after tax. Therefore, we suggest investing in RMFs first because of the ability to beat the market and tax benefit. Next, the investors should consider investing in LTFs, and the last choice should be EQs. Nevertheless, the tax benefit from RMFs and LTFs can be achieved only by long-term investment period. Furthermore, the management fees should be based on the risk-adjusted performance of funds instead of the net asset value, and all necessary information should be published to investors to reduce the information asymmetry problem and help investors in making an investment decision. Finally, the Thai government should further educate investors to improve knowledge related to investment in capital market to increase the educated investors in the market.